Understanding institutional change: A review of selected literature for the Climate Change and Rural Institutions Research Programme - Ida Peters; Ian Christoplos; Mikkel Funder; Esbern Friis-Hansen; Adam Pain (Danish Institute for International Studies (DIIS), 2012)
This literature review summarises selected theories of institutional change, with a particular emphasis on issues relevant to the Climate Change and Rural Institutions (CCRI) research programme. The review focuses on concepts that can be applied in understanding how and why meso level institutions operating at district and provincial levels respond or fail to respond when faced with climate change related upheavals. The review examines the concepts of path dependency, gradual institutional change and institutional bricolage, and how these tools might be used to understand processes of change in meso level institutions when faced by catastrophic environmental change.
Keywords: 300; Klimawandel; Institutioneller Wandel; Pfadabhängigkeit; Mesoökonomie